2011
DOI: 10.2134/agronj2010.0494
|View full text |Cite
|
Sign up to set email alerts
|

Barley Productivity Response to Polymer‐Coated Urea in a No‐Till Production System

Abstract: Farmers are interested in more cost-effi cient and environmentally sound fertilization programs in fi eld crops. A multi-site study on the Canadian prairies was conducted to determine the eff ect of polymer-coated urea (Environmentally Smart Nitrogen, ESN) compared with urea on weed management and barley (Hordeum vulgare L.) yield and quality. Treatments included a semi-dwarf and tall barley cultivar, polymer-coated urea (ESN) and urea, 100 and 150% of soil test N fertilizer rates, and 50 and 100% of registere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
2
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 37 publications
3
10
2
7
Order By: Relevance
“…The blended application produced yield and NR similar to those of SCRU or split applications of urea in other locations. The results are consistent with the results of Blackshaw et al (2011) where barley seed yield under ESN was not significantly different than with urea for most site-years. Barley NR showed a linear increase to N application in almost all sites, with a quadratic component only at Melfort andLacombe under RT in 2004.…”
Section: Results and Discussion Barley Net Revenuesupporting
confidence: 90%
See 2 more Smart Citations
“…The blended application produced yield and NR similar to those of SCRU or split applications of urea in other locations. The results are consistent with the results of Blackshaw et al (2011) where barley seed yield under ESN was not significantly different than with urea for most site-years. Barley NR showed a linear increase to N application in almost all sites, with a quadratic component only at Melfort andLacombe under RT in 2004.…”
Section: Results and Discussion Barley Net Revenuesupporting
confidence: 90%
“…Malhi et al (2010) also noted that the higher cost of CRU must be considered when choosing a fertilizer, since the agronomic benefit was not consistent. Blackshaw et al (2011) completed another study on the Canadian prairies that compared the impacts of ESN fertilizer and urea at different application rates on barley yield and quality. The study found that ESN improved yield at 3 of 20 site-years but yield was not significantly different from that of urea at 15 of the 20 site-years.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrate leaching is a greater risk when these N sources are applied in the fall. Several studies have evaluated response to enhanced-efficiency N fertilizer in wheat [13][14][15][16], canola (Brassica napus L.) [17,18], and barley (Hordeum vulgare L.) [19]. Wheat yield response varied based on management, application timing, application rate, and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat yield response varied based on management, application timing, application rate, and environmental conditions. Studies of small grains show that, in addition to yield impacts, protein concentration with PCU was similar or increased compared to urea [15,19]. It is critical to understand the possible utility of enhanced efficiency fertilizer sources in order to properly integrate this technology into Midwestern wheat production systems.…”
Section: Introductionmentioning
confidence: 99%